Plasmid vector(s) in Bacillus thuringiensis harbor genes for insect pest control and for neglected infectious diseases in humans - Guerrero, Gloria G.; Favela-Hernandez, Juan M.; Balderas-Renteria, Isaias (Frontiers in Tropical Diseases, 2024)
Plasmids (circular DNA molecules) represent an ingenious strategy for horizontal gene transfer in prokaryotes and eukaryotic cells. Plasmids harbored in bacteria are responsible for the spread of traits such as antibiotic resistance, virulence factors, and the machinery for the horizontal gene transfer e.g., type IV secretion systems. Remarkably, Bacillus thuringiensis (Bt) cryptic plasmids encode and carry genes that, under the host environment, replicate and concomitate with sporulation, producing parasporal crystalline proteins of two major types, crystalline (Cry) and cytolytic (Cyt), the former toxic against different orders of insects such as Lepidopterans, Coleopterans, and Dipterans (Cry proteins, MW 50–130 KDa); Cyt proteins, produced by B. thuringiensis subspecies israelensis (Bti)(MW 27-kDa) are toxic against Dipterans, i.e., mosquitoes and black flies. The X-Ray tridimensional structure for both types of toxins, formed by three domains, mostly of beta sheets antiparallel (Domain II and Domain III) linked through loops of different lengths. Domain I is a bundle of alpha helices. This structure is characterized by five conserved blocks, implying a conservation in the mode of action. Cyt proteins possess two alpha helices and some beta sheets with a structure similar to the antimicrobial peptides. Indeed, the mode of action proposed is mediated by the toxin-lipid interaction that hypothetically could result in transmembrane ionic channel formation. Several pieces of evidence support the action of both toxins in insects and mammals. The question is to what extent these Bt/Bti plasmid-encoded Cry or Cyt genes can be applied as bioinsecticides individually or in combination with Lysinibacillus sphaericus. The feasibility of being considered a promising and safe biological strategy for crop pests and vector-borne neglected infectious diseases is an issue pinpointed in the present review.